Perlindungan Hukum Terhadap Konsumen Dalam Jual Beli Pakaian Bekas (Thrifting) Melalui Aplikasi TikTok - Loemongga Arthamevia; Arif Awaludin; Ikama Dewi Setia Triana; Aniek Periani (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2024)
Abstract This research aims to provide an explanation regarding the legal provisions governing the legality of buying and selling second-hand clothing or thrifting through the TikTok application in Indonesia, as well as the protection offered by law to consumers who purchase second-hand clothing. To complement that objective, this research employs a Normative Juridical method using a Legislative approach. This research shows the following results: First, the practice of buying and selling second-hand clothing in Indonesia is not prohibited; however, if the second-hand clothing being sold is imported, this contradicts the Minister of Trade Regulation Number 51 of 2015 concerning the Prohibition of Importing Second-Hand Clothing and the Minister of Trade Regulation Number 40 of 2022 concerning Prohibited Export and Import Goods. Therefore, it is established that the activity of buying and selling imported second-hand clothing is ILLEGAL. Second, consumer protection in the buying and selling of second-hand clothing can be carried out in two ways: preventively, through the establishment of legislation on consumer protection, and repressively, through resolution between both parties (non-litigation) or by filing a lawsuit in the General Court (litigation). Keywords: Buying and Selling, Second-Hand Clothing, Import, Law, Consumer Protection.